A Systematic Review of User Mental Models on Applications Sustainability - Nasrudin, Nur Hasni; Ahmad, Samsiah; Ahmad Salleh, Khairulliza; Azahari, Lily Adina (International Journal of Sustainable Construction Engineering and Technology, 2023)
In Human-Computer Interaction (HCI), a user’s mental model affects application sustainability. This study's goal is to find and assess previous work in the area of user mental models and how it relates to the sustainability of application. Thus, a systematic review process was used to identify 641 initial articles, which were then screened based on inclusion and exclusion criteria. According to the review, it has been observed that the mental model of a user has an impact on the creation of applications not only within the domain of Human-Computer Interaction (HCI), but also in other domains such as Enterprise Innovation Ecology, Explainable Artificial Intelligence (XAI), Information Systems (IS), and various others. The examined articles discussed company managers' difficulties in prioritising innovation and ecology, and the necessity to understand users' mental models to build and evaluate intelligent systems. The reviewed articles mostly used experimental, questionnaire, observation, and interviews, by applying either qualitative, quantitative, or mixed-method methodologies. This study highlights the importance of user mental models in application sustainability, where developers may create apps that suit user demands, fit with cognitive psychology principles, and improve human-AI collaboration by understanding user mental models. This study also emphasises the importance of user mental models in the long-term viability and sustainability of applications, and provides significant insights for application developers and researchers in building more user-centric and sustainable applications.